Twinning in ART: Single embryo transfer policy. (November 2022) - Fouks, Yuval; Yogev, Yariv
Abstract: It is more than thirty years that perinatologists and healthcare personnel aim to reduce the morbidity associated with multiple pregnancy. In many cases, these complications stem from pregnancies achieved through artificial reproductive technologies (ART). Although dramatic measures have been taken to control those risks by increasing the proportion of single embryo transfers, the multiple pregnancy rate still remains relatively high among patient conceived through ART, carrying risks to both mothers and newborns, and is coupled with the related economic burden associated with prematurity. The aim of this review is to provide the current evidence regarding single embryo transfer to assist decision-makers and to promote patient knowledge toward an elective policy to reduce the risk of twinning. Single embryo transfer may aid in the further reduction of multiple pregnancy and, in most cases, will maintain patient autonomy and right of choice. Highlights: IVF clinics should consider a well-constructed institutional eSET protocols. When considering to transfer embryos, it is important that the caregiver will ensure the needs preference of the specific patient and long-term consequences of multiple pregnancy. ESET, in combination with frozen embryo transfer, is an effective strategy to decrease the multiple birth rates. There are insufficient data regarding the efficacy of eSET outcomes in women of advanced age.